Diagnóstico de Tuberculosis en Camélidos Sudamericanos en el CEYPSA - Chimarro Quishpe, Doris Narcisa (2017)
The present project aimed at the diagnosis of bovine tuberculosis (TBB) in alpacas and llamas carried out in the CEYPSA province of Cotopaxi, Latacunga canton Salache parish, Salache Bajo sector, located at 2750 m altitude with an average temperature of 12 ° C. For this purpose, 18 alpacas (9 females, 3 males) and 6 llamas (4 males and 2 females) were used in the Animal Science and Agricultural Sciences Faculty (CEYPSA). The relevant research was the diagnosis of tuberculosis in South American camelids (alpacas and llamas) for which the simple intradermotuberculation test (IDTB) was used, 1ml of tuberculin-derived purified bovine protein (PPD) strain (AN5) was inoculated into the Region of the right thoracic fold adjacent to the dorsal oleocranon process to the sternum in animals older than 6 months. After 72 hours of tuberculin application the thickness of the skin at the injection site was measured, resulting; 18 negative animals 6 flames and 12 negative alpacas tested, no animals showed evidence of any inflammatory reaction at the inoculation site and the differences of the averages were less than 1.5 mm, the mean pre-inoculation skin thickness was Of 2.5 mm and the mean of the postinoculation readings was 3 mm. In order to corroborate the response of the IDTB test after desensitization, 3 animals were selected from the total population and the interferon gamma test was performed, which yielded negative results, in this way it was concluded that the simple bovine intradermotuberculization The gamma interferon test applied on alpacas and llamas is a viable option to diagnose tuberculosis in South American camelids.